2023
DOI: 10.3390/biomedicines11041185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cold Atmospheric Plasma Pre-Treatment of Titanium on the Biological Activity of Primary Human Gingival Fibroblasts

Abstract: Cold atmospheric plasma treatment (CAP) enables the contactless modification of titanium. This study aimed to investigate the attachment of primary human gingival fibroblasts on titanium. Machined and microstructured titanium discs were exposed to cold atmospheric plasma, followed by the application of primary human gingival fibroblasts onto the disc. The fibroblast cultures were analyzed by fluorescence, scanning electron microscopy and cell-biological tests. The treated titanium displayed a more homogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The second contribution by the research group, "Cold Atmospheric Plasma Improves the Colonization of Titanium with Primary Human Osteoblasts: An In Vitro Study", by Madline P. Gund et al, investigates the effects of cold atmospheric plasma (CAP) treatment on titanium surfaces and its subsequent impact on primary human osteoblast colonization. The findings contribute to the growing body of evidence supporting the utility of cold atmospheric plasmas in biomedical applications, particularly in enhancing osteoblast colonization on implant surfaces [21].…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The second contribution by the research group, "Cold Atmospheric Plasma Improves the Colonization of Titanium with Primary Human Osteoblasts: An In Vitro Study", by Madline P. Gund et al, investigates the effects of cold atmospheric plasma (CAP) treatment on titanium surfaces and its subsequent impact on primary human osteoblast colonization. The findings contribute to the growing body of evidence supporting the utility of cold atmospheric plasmas in biomedical applications, particularly in enhancing osteoblast colonization on implant surfaces [21].…”
mentioning
confidence: 57%
“…Madline P. Gund et al's "Effects of Cold Atmospheric Plasma Pre-Treatment of Titanium on the Biological Activity of Primary Human Gingival Fibroblasts" explores the benefits of CAP treatment on titanium surfaces. The study suggests that CAP-treated titanium exhibits enhanced fibroblast coverage without altering biological behavior, offering insights into potential applications in implantology [21].…”
mentioning
confidence: 89%
“…The effects have previously been studied on primary human gingival fibroblasts and have shown that pre-treatment of titanium surfaces leads to improved initial adhesion of these cells [ 6 ]. To the best of our knowledge, this is the first study to demonstrate beneficial effects of cold atmospheric plasma to condition micro-structured titanium on the early attachment of primary human osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The peri-implant tissue acts as a barrier and protects against oral bacteria. Contamination of the implant surface by microorganisms can be prevented, thus avoiding inflammation of the surrounding tissue and bone [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation